Herpes Simplex Virus Infection Mimicking Bullous Disease in an Immunocompromised Patient - Lecluse, Anne L.Y. (S. Karger AG, 2010)
Immunodeficient patients are at risk of developing extended or atypical herpes simplex virus infections, which can be easily misdiagnosed. We present the case of a 79-year-old, treatment-induced (oral corticosteroid), immunocompromised female with an extensive atypical herpes simplex virus infection. This patient presented with multiple erosions and vesicles on the trunk with a subacute onset. The clinical differential diagnosis was herpes simplex infection, herpes zoster infection, pemphigus vulgaris or bullous pemphigoid. Due to the atypical clinical presentation and negative Tzanck test, suspicion of viral infection was low. High-dose steroid treatment was initiated. Subsequent histopathology, however, showed a herpes simplex virus infection. After discontinuing steroid treatment and initiating antiviral treatment, the patient recovered within a week. Emphasis must be placed on the importance of clinical awareness of extended and clinically atypical herpes simplex infections in immunocompromised patients. A negative Tzanck test does not rule out the possibility of a herpes infection.